Delivering Integrated Health Care: Role and Importance of Multidisciplinary Team Clinic Role and Importance of Multidisciplinary Team Clinic in Nineveh Province - Al-Rawee, Rawaa; Al-Fathy, Dr. Marab; Bashir Alsabee ., Dr. Waleed (Jour Med Resh and Health Sci, 2022)
Aim: To evaluate and assess the knowledge of specialist regardless to ther speciality about the Multidisplinary Team Clinic and highlighting the benefit, obstcals and management information in Nineveh Province as t pass through many political circumstances. Material and Method: A cross?sectional study was conducted between August to November 2021 among specialist working in Nineveh Health Directorate. Sample size was intended according to the established role 10% from the total number of each group and even more. The minimum calculated sample size was (242 ) participants. Doctors (161), Pharmacists (28), and Dentists (53). Questioners focus on demographical informations, knowledge of specialized doctors about MDT Clinics, benefit, obstacles and management information. Result: Specialist have good knowledge, and informations about the benefitwith the obstcals, for correlation and signifacncy, correlation is significant at the 0.01 level (2-tailed) through spearman test. Most of answers show significant relations. Conclusion: MDT has advantages for all institutions, patients, and medical professionals. The major objective of MDT is to provide all patients with high-quality, specialized medical care while advancing knowledge among MDT members.